Quality Management Process of Religious-Based Primary School Education - Natsir B. Koten; Digvijay Pandey (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to reveal in-depth and give meaning to the planning, control, and improvement of religion-based elementary school education quality. This research method uses a qualitative approach through a multicase study plan with a constant comparative method. The research locations were SD Onekore 2 Santa Ursula Ende, SDK Santo Antonius Ende 2, and MIN Ende. The informants in this research were the Principal and Teachers. Data collection techniques use in-depth interviews, participant observation, and documentation studies. A structured set of questions designed to elicit information from stakeholders such as teachers, administrators, parents, and students about their perceptions, experiences, and suggestions regarding quality management in primary education with a religious foundation. The research results show that the Religious Primary School Quality Management Process has a strong commitment, which the founders inherited, managers, and previous education staff, and is preserved, continued, and strengthened by the management and education staff in the future. The meaning of quality by the management and educational staff of religious-based elementary schools is more holistic; the students' personalities are intact, and the quality management of religious-based elementary schools consists of school quality planning, quality control, and quality improvement. Through the quality management process of religious-based elementary schools, the school has a strong commitment, inherited by the founder, managers, and previous education staff, and preserved, continued, and strengthened by managers and education personnel.